Analisis Kinerja Sistem Pengereman Pada Mobil Hemat Energi Bono Kampar - Meitryano, Denis; Syafri, Syafri; Anuar, Kaspul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
In designing a car that is comfortable and safe when driving, there are some things to watch out for, namely the steering system, brakes, and suspension. In this study, the authors will analyze about the braking system on the car Bono Kampar. The research of the braking system begins by searching for the specification data from Bono Kampar's car. After the data of Bono Kampar's car specification was obtained, then calculations were done to find the car's center of gravity, measure the dimensions of the braking system, calculate the braking distance, calculate the braking torque force, calculate the actual or theoretical braking proportions, calculate the vertical force, and analyze the theoretical stability or actual.From this study it can be concluded that the direction of behavior on Bono Kampar car is understeer according to the method theoretical and actual.Keyword :car, brake system, proportion of braking, stability of car direction.